Automated anomalies detection in the work of industrial robots; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Goncharov A. S. Arkady Sergeevich; Savelyev A. O. Aleksey Olegovich; Krinitsyn N.; Mikhalevich S. S. Sergey Sergeevich (2021, 2021)
Title screen